Clinical Practice, and Diagnosis and Treatment Strategies of Chronic Hepatitis D Virus (HDV) - Haradhan Kumar Mohajan (Innovation in Science and Technology, 2025)
Hepatitis is the liver inflammatory disease that gradually damages the liver. Hepatitis D/delta hepatitis is a liver infection caused by the hepatitis D virus (HDV). The HDV is a blood-borne pathogen and only occurs as either a co-infection with hepatitis B virus (HBV) or as a super-infection of persons with chronic HBV. It can be an acute for short-term infection or become a long-term chronic infection. In chronic infection HDV can cause serious liver damage (cirrhosis) and death at the end stage. The HDV infection is more common in Eastern Europe, South America, Africa, Central Asia, and the Middle East. At present no vaccine is available to prevent HDV. Vaccination against HBV provides the best prophylaxis against hepatitis D. The pegylated interferon alpha (Peg-IFNα) is the only therapy available to treat HDV infection that is associated with significant side-effects. Recently new medication bulevirtide, an HDV entry inhibitor, is approved to treat it. In this study, I have tried to discuss the virology, transmission, diagnosis, and treatment of the HDV infection.